Mi experiencia docente en el contexto de las aulas costarricenses: el disfrute de retomar las acciones del pedagogo, inspiraciones en el Repertorio Americano - Loáiciga Brenes, Saray Elena (2018)
During our own praactice, we find a great diversity of students who have stories, different ways of breeding, rhythm and styles of their own learning, which make us inspire our academic and comprehensive training efforts; to help them is the most wonderful satisfaction and why we teach. There are hundreds of human faces that make the task of educating. And behind them an inspiring educator who helped to confirm the orientation for the art of education. Therefore, this work makes a tour of several rewarding experiences of educators and artists who paint the future of many to be the bulwarks of a caring society.